Pengaruh Rasio Likuiditas, Solvabilitas dan Profitabilitas Terhadap Kinerja Keuangan pada Sub Sektor Perbankan Konvensional yang Terdaftar di Bursa Efek Indonesia Periode 2013-2017 - Fuji Harianto; Ika Zutiasari (Prodi Akuntansi Fakultas Ekonomi Universitas Hasyim Asy'ari, 2020)
This research has purpose to test the influence of liquidity ratio with formula Loan to Deposit Ratio (LDR), solvency ratio with formula Capital Adequacy Ratio (CAR) and profitability ratio with operating expense operating income (BOPO) toward financial performance with formula Return on Asset (ROA). This research using time series data from financial report and annual reports banking firms wich listed on BEI. After passed the purposive sampling phase, then the sample that are worth using are 32 banking companies firms wich listed on BEI. The analysis technique used is multiple regression analysis. From the F test shows that of liquidity, solvency and profitability variable simultaneously affect significantly to financial performance Return On Asset (ROA). The result of t test shows that liquidity ratio (LDR) and solvency (CAR) variables has not significant effect to the financial performance (ROA). Profitability (BOPO) variable has a negative and significant effect to the financial performance (ROA).